Morphological characterization of Kenyan native wood ear mushroom [Auricularia auricula (L. ex Hook.) Underw.] and the effect of supplemented millet and sorghum grains in spawn production - Gichimu, Bernard M.; Palapala, V.A; Arama, P.F; Wagai, S.O. (My University, 2011)
Utilization of mushrooms collected from the wild requires adequate description of useful phenetic features and domestication protocols. This study investigated morphological characters and spawn production procedures of three Kenyan native strains of wood ear mushroom [Auricularia auricula (L. ex Hook.) Underw.]. Nine basidiocarps were selected from collections made in three forest reserves within Kakamega Forest in Western Kenya and morphologically characterized. Mycelia were raised on 2% malt extract agar and bottle culture technology was used for spawn production. The spawning experiment was arranged in completely randomized design with three replicates. Variations occurred in external basidiocarp features such as color, texture, shape and presence of veined surfaces. Microscopic analysis of internal basidiocarp structures did not reveal significant differences. However, external features of mycelia colonies varied when cultured in malt extract agar. Results from spawn production showed that supplemented millet and sorghum grains can be successfully colonized by mycelia to produce high quality spawn.
Keywords: Morphological characterization; Spawn production; Kenya